Images of women in online advertisements of global products: Does sexism exist? - Plakoyiannaki, Emmanuella; Mathioudaki, Kalliopi; Dimitratos, Pavlos; Zotos, Yorgos (My University, 2008)
Research on female stereotypes in online advertisements is particularly scant, and thus, we lack evidence on whether women are depicted in derogatory (stereotypical) terms on the Internet or not. This theme has significant ethical implications. Hence, the objectives of this study are: (1) to provide evidence on female role portrayals in online advertisements of global products, and (2) to explore female role portrayals across web pages for different audience types. The results indicate that women are generally portrayed in a stereotypical way, supporting the notion that sexism is prevalent in online advertisements worldwide. Portrayal of women across web pages varies considerably, with female-audience web pages embracing "decorative" female images; male-audience web pages promoting polarizing depictions of women in "dependent" or "non-traditional" roles; and general-audience web pages using portrayals of women as housewives or equal to men. Overall, the findings suggest that "traditional" or "decorative" stereotypes are largely evident in all three audience types, although some "non-traditional" roles may occur. Implications and future research directions are discussed.
Keywords: Female role stereotypes; Global products; Online advertisements; Sexism